Exploring students' self-efficacy and anxiety towards mathematics problem solving during Open and Distance Learning (ODL) / Nurul Syahmi Hamizah Amiruddin, Noraini Ahmad and Siti Salwana Mamat - Amiruddin, Nurul Syahmi Hamizah; Ahmad, Noraini; Mamat, Siti Salwana (Universiti Teknologi MARA, Perak, 2022)
Although mathematics is seen as a crucial precursor to success in modern society, many students still struggle with real mathematical fear. They feel anxious when they engage in solving mathematical problems, especially in the last two years when the learning environment has changed due to the epidemic. One of the affective factors that can influence mathematical anxiety is the beliefs of students about their own ability to resolve issues called self-efficacy. The aim of this research is to explore student self-efficacy and anxiety in solving math problems among high school students during open and distance learning (ODL). The research used a quantitative analytical approach. A survey of 138 students was carried out on forms 1 and 4 at one of the secondary schools in Kota Bharu, Kelantan. The survey follows Diana May's Mathematical Questionnaire on Self-Effectiveness and Anxiety (MSEAQ). The data were analyzed in SPSS using descriptive statistics, an independent sample t-test, and a simple linear regression. The results showed that descriptive statistics had a lower level of self-efficacy and a higher level of mathematical anxiety among Form 1 and Form 4 students. An independent sample t-test revealed no significant difference between lower and upper secondary school students in self-efficacy and anxiety towards mathematics problem solving which means that lower and upper secondary school students can have the same level of mathematics self-efficacy and anxiety. Simple linear regression shows a moderately significant negative linear relationship between mathematics self-efficacy and anxiety. This paper presents an overview of students' self-efficacy and anxiety toward math subjects during secondary school.